Marked gut microbiota dysbiosis and increased imidazole propionate are associated with a NASH Göttingen Minipig model - Ditte Olsen, Lützhøft; Tim, Sinioja; Berit Ø., Christoffersen; Jakobsen, Rasmus Riemer; Dawei, Geng; Hajar Fauzan, Ahmad; Ellen Marie, Straarup; Karen-Margrethe, Pedersen; Kot, Witold; Henrik Duelund, Pedersen; Susanna, Cirera; Tuulia, Hyötyläinen; et al. (Springer Science and Business Media LLC, 2022)
Background: Gut microbiota dysbiosis is associated with the development of non‑alcoholic steatohepatitis (NASH) through modulation of gut barrier, inflammation, lipid metabolism, bile acid signaling and short‑chain fatty acid production. The aim of this study was to describe the impact of a choline‑deficient amino acid defined high fat diet (CDAHFD) on the gut microbiota in a male Göttingen Minipig model and on selected pathways implicated in the development of NASH. Results: Eight weeks of CDAHFD resulted in a significantly altered colon microbiota mainly driven by the bacterial families Lachnospiraceae and Enterobacteriaceae, being decreased and increased in relative abundance, respectively. Metabolomics analysis revealed that CDAHFD decreased colon content of short‑chain fatty acid and increased colonic pH. In addition, serum levels of the microbially produced metabolite imidazole propionate were significantly elevated as a consequence of CDAHFD feeding. Hepatic gene expression analysis showed upregulation of mechanistic target of rapamycin (mTOR) and Ras Homolog, MTORC1 binding in addition to downregulation of insulin receptor substrate 1, insulin receptor substrate 2 and the glucagon receptor in CDAHFD fed minipigs. Further, the consequences of CDAHFD feeding were associated with increased levels of circulating cholesterol, bile acids, and glucagon but not total amino acids. Conclusions: Our results indicate imidazole propionate as a new potentially relevant factor in relation to NASH and discuss the possible implication of gut microbiota dysbiosis in the development of NASH. In addition, the study emphasizes the need for considering the gut microbiota and its products when developing translational animal models for NASH.